Impact of Economic Downturn on Child Labor in Vietnam - Huyen, Nguyen Thanh (Lentera Hukum, 2021)
The economic recession led to the economic downturn, loss of jobs and income, and the risk of falling back into the poverty of near-poor and poor households. This recession caused an increase in child labor. This study aimed to analyze the concept of child and child labor under a regulatory framework and assess how the economic downturn affects child labor in Vietnam. This study used analytical research methods through synthesis, comparison, and legal analysis, emphasizing literary research based on secondary research data. This study showed that the economic downturn increased the proportion of child labor because the parents and the family's breadwinner are unemployed or cut down on their income. Children were out of school to help household businesses or look for work for extra income. The economic downturn increased the number of children working in unsafe working conditions. It increased the risk of children being forced into illegal jobs prohibited and exposing children to labor to risk forced labor. It resulted in difficulties preventing and eliminating child labor, especially in a developing country like Vietnam, due to the high number of employees working in the informal sector, who were often unsupported by social security policies such as unemployment insurance and social insurance. This study suggested that the Government should establish policies to promote sustainable economic development and promulgate appropriate social security policies to promptly support workers and their families out of difficulties caused by job loss. Also, it should organize the effective implementation of regulations on eliminating child labor and raise social awareness in preventing and eliminating child labor. KEYWORDS: Economic Downturn, Child Labor, COVID-19 Pandemic.